Perancangan Aplikasi Berbasis Web Sebagai Alat Pendukung Keputusan Dalam Memilih Ac Hemat Energi - ., Maimuzar; Sumiati, Ruzita; ., Haris; Leni, Desmarita; Dwiharzandis, Aggrivina (Rekayasa Material, Manufaktur dan Energi, 2023)
The increase in global energy demand has driven the need for efficient solutions in selecting energy-efficient air conditioners (ACs). This research focuses on designing a web-based application as a decision support tool for choosing energy-efficient ACs. Energy-efficient labeled AC data is obtained from the Directorate General of New and Renewable Energy and Energy Conservation (EBTKE) website. This database is processed according to the system's requirements, where each AC brand is evenly represented to prevent dominance by a few brands. There are 11 different AC brands in this dataset, and each brand has 10 data samples. The web-based application is developed using the Python programming language with the Streamlit framework. This application allows users to compare various AC brands by considering power, annual energy consumption, efficiency value, and electricity cost. In the application design, users can select AC brands according to their needs, set the operating duration, choose the AC efficiency level, and select the inverter AC type. The application presents comparisons in the form of bar charts, making it easy for users to understand the differences in AC characteristics. The average results from the efficiency comparison of each AC brand reveal that Daikin achieves the highest efficiency at 16.36 Energy Efficiency Ratio (EER), while the GREE brand has the lowest efficiency at 5.83 EER. This application can assist consumers and industrial AC stakeholders in making decisions to choose energy-efficient ACs according to their needs.